REAL EARNINGS MANAGEMENT AND FIRM VALUE: THE ROLE OF INSTITUTIONAL OWNERSHIP AS MODERATING VARIABLE - Ni Luh Putu Nirmala Jayanti; Dewa Gede Wirama (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
Firm value can be seen as the perception of investors in assessing the success of a firm through share prices. The share valuation that investors often use is PBV with the expectation of gaining profits. Managers are motivated to maintain profits with various efforts, such as real earnings management (REM). This study aims to obtain empirical evidence of the effect of REM on firm value moderated by institutional ownership. The research focuses on infrastructure firms listed on the Indonesia Stock Exchange during 2021-2023. The research method uses non-probability sampling, purposive sampling technique as many as 83 observations. Firm value is measured by PBV, REM is measured by Roychowdhury's 2006 model, and institutional ownership is calculated by the institutional shares divided by total outstanding shares. Through MRA analysis, it is obtained that REM has a negative effect on firm value and institutional ownership weakens the influence of real earnings management on firm value. The theoretical implications of this research are to confirm agency theory and the contingency approach. On the other hand, the practical implication is that it is important for investors and potential investors to be more careful in assessing the profit quality and company performance as a basis for taking decisions.